Pengaderan Pemimpin GKII Daerah Melawi Hilir Wilayah Kalimantan Barat - Beriang, Senan (Jurnal Kala Nea, 2024)
The objectives of writing this research are: First, so that the leaders, in this case the Regional Chairperson and the Related Commissions, can work together with the workers and all local congregations of the GKII Melawi Hilir Region of West Kalimantan to realize the importance of the leader formation program. Second, by implementing a serious cadre program, it is hoped that the Melawi Hilir Regional GKII will have professional leaders, managers and administrators in the future, who have solid character, knowledge and skills, and are ready to face various challenges and the rapid globalization of the world. The scope of the GKII Melawi Hilir Regional leader training, contains leader training, manager training, administrator training, and a summary. The leader development strategy of the GKII Melawi Hilir Region contains: Planning of leader training, implementation of leader training, evaluation for improving leader performance, leader placement, and summary.